БАСЛАЎЫШ КЛАСС ОҚЫЎШЫЛАРЫН ЎАТАНПАРЎАРЛЫҚ РУЎХЫНДА ТӘРБИЯЛАЎДА ФОЛЬКЛОРДЫҢ КИШИ ЖАНРЛАРЫНЫҢ ТУТҚАН ОРНЫ - Алламбергенов, К.; Пазылов, Т.А. (FAN va JAMIYAT, 2022)
The article discusses the role of small genres of folklore in educating primary school students in the spirit of patriotism. Methods of teaching based on the patriotic idea of small genres of folklore are also given.